Application Of Hallimond Tube For Flotability Study Of Magnetite - Zulkarnain, ‘Aainaa Shahirah (Universiti Sains Malaysia, 2022)
This project focused on studying the effect of varied parameters on recovery of magnetite. For example, pH, conditioning time, collector dosage, flotation time and maleic acid as a collector are the parameters that been study for. The optimum parameter, which gave the maximum recovery on each variable was determined. The experiment was conducted in a Hallimond tube by using sample of having 96.81% of iron oxide. Oleic acid and maleic acid were employed as collector. Based on the results obtained, it showed that oleic acid is the efficient collector for flotation of magnetite. Magnetite float better on the alkaline phase with pH of 11. Other than that, for best conditioning time, it showed that 8 minutes is the ideal time for flotation of magnetite. For the collector dosage, the results showed that the best dosage of collector was 300 g/t with maximum recovery. Furthermore, the flotation time of 8 min gave the maximum recovery of magnetite. Different collector was used which is maleic acid to investigate the performance and it showed that maleic acid has less recovery compared to oleic acid with the recovery of 39.63%.